Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Ayam Penyet Sambel Pecak Kak Juli - Mahardika, Pinkan; Febrina , Annisa (Journal of Community Research and Service, 2025)
This study aims to find out and analyze the influence of Product Quality, Price and Service Quality onCustomer Satisfaction. The location of the research was carried out at Ayam Penyet Sambel Pecak Kak Juli. Thesample in this study was 85 people. The analysis method in this study is multiple linear regression analysis andprocessed with the help of SPSS v. 25. The results of the study showed that there was a significant influencebetween Product Quality and Customer Satisfaction in Chicken Penyet Sambel Pecak Kak Juli. There is asignificant influence between Price on Customer Satisfaction in Chicken Penyet Sambel Pecak Kak Juli. Therewas no significant influence between Service Quality and Customer Satisfaction at Chicken Penyet Sambel PecakKak Juli. Meanwhile, simultaneously Product Quality, Price and Service Quality simultaneously have asignificant effect on Customer Satisfaction at Chicken Penyet Sambel Pecak Kak July. The contribution of theinfluence of these variables is 30.2%.